Threats of global warming to the world’s freshwater fishes - Valerio Barbarossa (Nature Portfolio, 2021)
Climate change is a threat to global biodiversity, but the potential effects on freshwater fishes have not been well studied. Here the authors model future flow and water temperature extremes and predict that increases in water temperature in particular will pose serious threats to freshwater fishes